Is the admission test for a course in medicine a good predictor of academic performance? A case−control experience at the school of medicine of Turin. Issue 11 (1st December 2017) - Migliaretti, Giuseppe; Bozzaro, Salvatore; Siliquini, Roberta; Stura, Ilaria; Costa, Giuseppe; Cavallo, Franco
Abstract : Objectives: The usefulness of university admission tests to medical schools has been discussed in recent years. In the academic year 2014–15 in Italy, several students who failed the admission test appealed to the regional administrative court ('Tribunale Amministrativo Regionale'—TAR) requesting to be included, despite their test results, and all were admitted to their respective courses. The existence of this population of students generated a control group, in order to evaluate the predictive capacity of the admission test. The aim of the present work is to discuss the ability of university admission tests to predict subsequent academic success. Setting and participants: The study involved 683 students who enrolled onto the first year of the degree course in medicine in the academic year 2014–15 at the University of Turin (Molinette and San Luigi Gonzaga colleges). The students were separated into two categories: those who passed the admission test (n1=531) and those who did not pass the admission test but won their appeal in the TAR (n2=152). Outcomes: The validity of the admission test was analysed using specificity, sensitivity, positive and negative likelihood ratios (LH+, LH−), receiver operating characteristic (ROC) curves, area under the ROC curve (AUC), and relative (95% CI). Results: The results showed that the admission test appeared to be a good tool for predicting the academic performances in the first year of the course (AUC=0.70, 95% CI 0.64 to 0.76). Moreover, some subject areas seemed to have a greater discriminating capacity than others. In general, students who obtained a high score in scientific questions were more likely to obtain the required standards during the first year (LH+ 1.22, 95% CI 1.14 to 1.25). Conclusions: Based on a consistent statistical approach, our study seems to confirm the ability of the admission test to predict academic success in the first year at the school of medicine of Turin.